China's Next Strategic Advantage - Yip, George; McKern, Bruce (Tantor Media, Inc., 2016)
The history-making development of the Chinese economy has entered a new phase: China is moving aggressively from a strategy of imitation to one of innovation. Driven both by domestic needs and by global ambition, China is establishing itself at the forefront of technological innovation. Western businesses need to prepare for a tidal wave of innovation from China that is about to hit Western markets, and Chinese businesses need to understand the critical importance of innovation in their future. In China's Next Strategic Advantage, experts George S. Yip and Bruce McKern explain this epic transformation and propose strategies for both Western and Chinese companies. This book is for everyone who does business with China or in China, or is interested in the development of the world's fastest-growing economy. Western CEOs can learn from Chinese companies and can create an effective innovation process in China, for China and the world. Chinese CEOs can benefit from understanding the strategies of their peers as they strive to enter foreign markets, and all Western businesses should prepare for disruption from their new competitors.